PrefikS um dalam bahasa Mandailing dialek Panyabungan = The Prefix um In the Penyambungan Dialect of the Mandailing Language - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
In BMDP Bahasa Mandailing Dialek Panyabungan = the Panyabungan Dialect of the Mandailing Language (PDML)) two linguistic forms /urn" and /-um-/ that have equal form and meaning are found. The problem that may arise is whether the two linguistic forms are allomorphs of the same morpheme or separate morphemes that stand alone. To solve the problem, theory that stresses on the importance of form and meaning for identifying a morpheme is adopted. By using this theory, it can be stated that the forms /um-/ and /-um-/ are allomorphs of the same morpheme, that is (um-). The morphophonemic proivss in forming prefix /um-/ and Aum-/ is eau sPei by phonological constraints. Then the morpheme (urn) can be identified as a prefix that can stand by itself Prefix [urn-) has a parallel distribution with suffix (-an). The two affixes can be combined with the same stern and produce the same meaning.